MANAJEMEN PENDIDIKAN DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN BUSTANUL QURAN ASSURYANIYAH KECAMATAN MUSTIKA JAYA KOTA BEKASI - Elis Apriyanti Rahman (UNISAN JURNAL, 2024)
These researches used are, First, to description of plan of education disciplinary students in Bustanul Quran Assuryaniyah Islamic Boarding School. Secondly, to description of implementation of education disciplinary students in in Bustanul Quran Assuryaniyah Islamic Boarding School. Third,to description of monitoring of education disciplinary students in Bustanul Quran Assuryaniyah Islamic Boarding School.This research used a qualitative approach with case study, and the data collection used by interview, observation, and documentation, Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions or verification, than informant of this research are guidance of students and students The results of the research are: 1) Planning: planning the goals of disciplinary education for students according to the vision, mission, and goals of the At Bustanul Quran Assuryaniyah Islamic Boarding School. ; making disciplinary rules for students; making guidelines for violations and penalties that will be given to disciplinary violators; and setting a schedule for disciplinary activities for students. 2) Implementation: providing direction for student discipline education; motivating students to participate in student discipline education; leading the course of student discipline education; communicating with students to ensure student discipline education understanding; and making decisions on actions that violate student discipline. 3) Supervision: direct supervision includes court and attendance readings; indirect supervision includes performance evaluation.